Examination of the effect of individual innovation on entrepreneurship and problem solving skills in midwifery students - Sunay, Zeliha; Ulutaş, Ümmügülsüm; Yılmaz, Ayşe Nur (Tuba UÇAR, 2021)
Aim: The study was conducted to determine the effects of individual innovativeness characteristics on individual entrepreneurship perception and problem solving skills in midwifery students. Methds: The sample of the study, which is descriptive and relationship seeker, consisted of 538 students who were studying at Inonu University, Fırat University and Munzur University Faculty of Health Sciences Department of Midwifery between March-April 2020 and accepted to participate in the study. Data were collected online using the Personal Information Form, Individual Innovativeness Scale (IIS), Individual Entrepreneurship Perception Scale (IAS) and the Problem Solving Inventory (PSI). Results: The total score average of the students from the IIS, IAS and PSI was 65.22 ± 8.84, 66.76 ± 18.87 and 91.95 ± 15.67,respectively. According to individual innovation characteristics such as innovative, pioneering, questioning, skeptical and traditionalist, the difference between the overall average score obtained from IIS, IAS and PSI was statistically significant (p<0.05). In addition, a negative significant correlation was found between IIS, IAS and PSI (r=-0.097 p <0.001; r=-0.274 p<0.001, respectively) and a significant correlation was found between the Pioneer, interrogator and skeptical characteristics of students and the IAS and between the Pioneer characteristic and the PSI according to the individual characteristics of innovation (r= 0.171 p<0.05; r= -0.148 p<0.05; r= -0.270 p<0.05; r= -0.223 p<0.05, respectively). Conclusion: It was determined that there is a statistically significant difference between the individual innovativeness characteristics of the students and their entrepreneurship perception and problem solving skills.

Amaç: Araştırma ebelik bölümü öğrencilerinde bireysel yenilikçilik özelliklerinin, bireysel girişimcilik algısına ve problem çözme becerisine etkisini belirlemek amacıyla yapılmıştır. Yöntem: Tanımlayıcı ve ilişki arayıcı tipte ki bu araştırmanın örneklemini, Mart-Nisan 2020 tarihleri arasında İnönü Üniversitesi, Fırat Üniversitesi ve Munzur Üniversitesi Sağlık Bilimleri Fakültesi Ebelik Bölümünde ki araştırmaya katılmayı kabul eden 538 öğrenci oluşturdu. Veriler online olarak, Kişisel Bilgi Formu, Bireysel Yenilikçilik Ölçeği (BYÖ), Bireysel Girişimcilik Algı Ölçeği (BGAÖ) ve Problem Çözme Envanteri (PÇE) ile toplandı. Bulgular: Öğrencilerin BYÖ’den aldıkları toplam puan ortalaması 65.22±8.84, BGAÖ’den aldıkları toplam puan ortalaması 66.76±18.87 ve PÇBE’den aldıkları toplam puan ortalaması ise 91.95±15.67’dir. Öğrencilerin yenilikçi, öncü, sorgulayıcı, kuşkucu ve gelenekçi gibi bireysel yenilikçilik özelliklerine göre BYÖ, BGAÖ ve PÇE’den aldıkları toplam puan ortalamaları arasındaki fark istatiksel olarak anlamlı bulunmuştur (p<0.05). Ayrıca BYÖ ile BGAÖ ve PÇE arasında negatif yönde anlamlı korelasyon bulundu (sırasıyla r=-0.097 p<0.001; r=-0.274 p<0.001) ve öğrencilerin bireysel yenilikçilik özelliklerine göre Öncü, Sorgulayıcı ve Kuşkucu Özellikleri ile BGAÖ arasında ve Öncü özelliği ile PÇE arasında anlamlı korelasyon bulundu (sırasıyla r=0.171 p<0.05; r=-0.148 p<0.05; r=-0.270, p<0.05; r=-0.223, p<0.05). Sonuçlar: Öğrencilerin bireysel yenilikçilik özellikleri ile, problem çözme becerisi ve girişimcilik algısı arasında istatistiksel olarak anlamlı bir fark olduğu belirlendi.
Ebelik öğrencilerinde bireysel yenilikçiliğin girişimcilik ve problem çözme becerilerine etkisinin incelenmesi
Keywords: Midwifery (Other); Ebelik (Diğer)